Disrupsi Nilai Keagamaan dalam Dakwah Virtual di Media Sosial Sebagai Komodifikasi Agama di Era Digital - L. Rudy Rustandi (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2020)
In addition to being a necessity, the phenomenon of online social media usage of the community has its own complexity in a community order. Facebook is one of the online social media that is on the platform initially intended for virtual social networking. The goal began to shift as the community needs and social media development itself. People have used it to achieve economic, social and even religious objectives. This research aims to know deeply the meaning behind the phenomenon disruption religious value on social media Facebook. The methods used in these study used qualitative methods. While the approach in this study used a thick description theory approach presented by Clifford Greetz. The results gained in this study were in-depth descriptions of the social dynamics of the community on Islamic ideology and political conflicts in Indonesia.